Influence of Anthropogenic Factors of the Industrial Production on the Quality of Life of the Population in the Region - Belik, Irina Stepanovna; Kamdina, Lyudmila Vladimirovna; Starodubets, Natalia Vladimirovna (Economy of Regions, 2019)
In the contemporary world, the anthropogenic effect is increasing. At the same time, the quality of life of the population is strongly associated with the environmental quality, as there is growing understanding that rising economic income does not ensure the humanity's well-being. In this regard, issues connected with analysing the influence of the anthropogenic factor on changes in the quality of the life of the population become relevant. We believe that existing approaches to assessing the quality of life poorly reflect the current situation related to the speed of the environmental changes due to an increase in the scale and intensity of its pollution. Therefore, for assessing the quality of life, we suggest taking into account the environmental and energy components ofthe anthropogenic factor. To this end, the classification of anthropogenic factors is supplemented by the “industrial production” group, distinguished by the “source of impact” indicator, which allows analysing the groups influence on changing parameters ofthe quality of life ofthe population. The methodological basis ofthe study is a comprehensive approach to assessing the quality of life. Based on it, we structured the stages of the evolution of approaches to measuring and assessing the quality of life ofthe population. Moreover, we described key features of these approaches, and identified the fourth stage that substantiates the priority of environmental and energy criteria in assessing the quality of life. We propose to improve the methodology for assessing the quality of life of the population by introducing additional environmental and energy characteristics. The article presents the results of using this improved methodology. We tested it on the examples ofthe Sverdlovsk and Chelyabinsk regions. The obtained values of the integral indicators of the quality of life of the population show that the Sverdlovsk region has lower index values. That happened due to a more developed industrial sector and, as a result, the more deteriorated environmental situation. The proposed methodology for assessing the quality of life ofthe population can be used by regional leaders for making decisions related to the regional development aimed at improving the quality of life of the population.